The Moderating Effect Of Perceived Organizational Culture On The Relationship Between Budget-Related Behaviour And Propensity To Create Slack For Yemeni Managers - Abdulqader, Abdulwahab Yahya Mohammed (2012)
The accounting researchers proposed that the propensity to create slack could leads to inefficient use of the resources that the organization controls. They also suggested that slack can be increased or decreased by several factors, including the budgetrelated behaviour. However, the results of prior studies examining the relationship between budget-related behaviour (such as participation, measure and monitor and evaluation by budget) and propensity to create slack is not clear and have often been found to be contradictory. As a result, many researchers have reconciled the inconsistent results by using the contingency approach. The present study aims to extend this line of research by examining another contingent variable, namely the managers’ perceptions of the organizational culture.